Hijacking limitations of working memory load to test for composition in language - Ullman, Michael T.; Bulut, Talat; Walenski, Matthew (My University, 2024)
Although language depends on storage and composition, just what is stored or (de)composed remains unclear. We leveraged working memory load limitations to test for composition, hypothesizing that decomposed forms should particularly tax working memory. We focused on a well-studied paradigm, English inflectional morphology. We predicted that (compositional) regulars should be harder to maintain in working memory than (non-compositional) irregulars, using a 3-back production task. Frequency, phonology, orthography, and other potentially confounding factors were controlled for. Compared to irregulars, regulars and their accompanying -s/-ing-affixed filler items yielded more errors. Underscoring the decomposition of only regulars, regulars yielded more bare-stem (e.g., walk) and stem affixation errors (walks/walking) than irregulars, whereas irregulars yielded more past-tense-form affixation errors (broughts/tolded). In line with previous evidence that regulars can be stored under certain conditions, the regular-irregular difference held specifically for phonologically consistent (not inconsistent) regulars, in particular for both low and high frequency consistent regulars in males, but only for low frequency consistent regulars in females. Sensitivity analyses suggested the findings were robust. The study further elucidates the computation of inflected forms, and introduces a simple diagnostic for linguistic composition.
Keywords: Composition; Irregular; Language; Morphology; Regular; Working Memory